Folk taxonomy of wild mushrooms in communities of the indigenous groups Chatino, Chontal, and Chinantec in Oaxaca, Mexico - Alexanders López-García; Marko Gómez-Hernández; Etelvina Gándara (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Traditional names of wild mushrooms have long served as crucial links between these organisms and humans. In Mexico, cultural groups traditionally use indigenous and Spanish names and have developed effective methods for classifying and naming mushrooms. This has allowed the suitable use of fungal resources and the transmission of ancestral knowledge regarding each species. The present study explores the folk taxonomy of wild mushrooms in communities belonging to the Chatino, Chontal, and Chinantec indigenous groups of Oaxaca, Mexico. The goal was to assess the origins and meanings of the mushroom names, their connections to local culture, and the similarities in folk taxonomy among indigenous groups to understand the dynamics of classification and assignment of names. Methods Between April and October 2022, 10% of the inhabitants in each community, including children, youth, adults, and elderly individuals, were interviewed to gather information related to their knowledge of wild mushrooms. Local translators assisted in analyzing the origins and meanings of mushroom names. Field trips to collect sporomes were conducted with community members. Regression analysis and analysis of covariance were performed to assess the use of traditional names among community members. Results A total of 43 indigenous names were recorded for 32 mushroom species. The Chatino people use 22 indigenous names for 23 species and refer to mushrooms as "Kía"; the Chontal group uses 15 names for 16 species, and the term for mushrooms is "Jlapilí"; the Chinantec group has six names for six mushroom species and uses the generic term "Naẗ." Indigenous names consist of a generic term for mushroom and a specific suffix. Since the mushroom names are assigned based on ecological, morphological, and cultural factors, similarities in their meanings can be observed among the communities. People’s age is positively related to the number of indigenous mushroom names they use. Women use more Spanish names than men. Conclusions The variety of names used in each studied community underlines the relevance of wild mushrooms for these indigenous groups. They have developed a comprehensive folk taxonomy that enables them to effectively utilize fungal resources and ensure the transmission of traditional knowledge.